Benin : Second Review under the Extended Credit Facility and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2018)
Economic growth remains strong, driven by cotton production, increased public investment, and a vibrant tertiary sector that benefited from the economic recovery in Nigeria since June 2017. The fiscal consolidation path envisages a lower than originally programmed fiscal deficit (including grants) in 2018-thanks to stronger domestic revenue mobilization-and attainment of the WAEMU convergence criterion of 3 percent of GDP in 2019. Program implementation remains satisfactory with all end-December 2017 quantitative performance criteria (QPCs) met. The ongoing rebasing of the national accounts initiated in 2017 is expected to be completed later in 2018.